Taphonomic and archaeological perspectives from northern Tierra del Fuego, Argentina - Borrazzo, Karen Beatriz (2015)
This paper focuses on Late Holocene coastal occupations of hunteregatherers that inhabited the northern steppes of Grande Island of Tierra del Fuego. Available archaeological data produced by our previous research in the Argentine portion of the island located north of San Sebastian Cape is discussed from a regional taphonomy perspective. Our approach is based on the characterization of the main taphonomic modes recognized in the region. Preservational and other patterns for bones and lithics are presented and discussed. Based on the comparative study of isotaphonomic assemblages, general trends in human coastal occupations are discussed.